IMPROVING TEACHER CREATIVITY THROUGH STRENGTHENING SELF-EFFICACY, KNOWLEDGE SHARING, AND TRANSFORMATIONAL LEADERSHIP : Empirical Research Using Correlational Methods and SITOREM Analysis of Private Elementary School Teachers at Buddhist Religious Foundations throughout Banten Province - Puja Subekti; Didiek Notosudjono; Rita Retnowati (AGUSPATI Research Institute, 2023)
Excellent quality of education is the foundation of the nation's progress. The realization of the quality of education is achieved through improving the quality of teaching. Teacher creativity has an impact on the quality of teaching and determines the achievement of school education goals and national education goals. It is very important to carry out in-depth studies on strategies for increasing teacher creativity. This study examines the increase in teacher creativity through strengthening self-efficacy, knowledge sharing and transformational leadership. This study aims to find strategies and ways to increase the creativity of teachers who teach at the elementary school level. Elementary school is the foundation for character building and key skills. This study uses a correlational method and is followed by an analysis of the Scientific Identification Theory to Conduct Operations Research in Education Management (SITOREM). The population of this study is 202 teachers who teach in private elementary schools at Buddhist religious foundations throughout Banten province, the sample size is 135 teachers. The results of the study show that there is a positive and significant relationship between Self-Efficacy, Knowledge Sharing and Transformational Leadership Together with Teacher Creativity. Increasing Teacher Creativity can be done by strengthening the variable indicators of Self-Efficacy, Knowledge Sharing and Transformational Leadership. Based on the STOREM analysis, there are 12 indicators that must be prioritized for improvement, and 7 indicators to be maintained.